Contribución del Instituto Brasileño de Información en Ciencia y Tecnología a la promoción del acceso abierto y la ciencia abierta: Análisis de sus infraestructuras - de-Freitas-Campos, Fhillipe; Machado-Borges-Sena, Priscila; Ribeiro-de-Carvalho-Segundo, Washington-Luis; Amaro, Bianca; Vilas-Boas, Raphael-Faria (Revista Científica, 2023)
Historically, scientific communication was dominated by marketing dynamics in which oligopolies of commercial scientific publishers charged high fees so that researchers could have access to the scientific publications of their peers. Given the unsustainability of this model for the scientific community, the Open Access Movement first emerged and, more recently and with new contributions, open science. Faced with this context, and aware of the competences for which it was founded, the Brazilian Institute of Information in Science and Technology (Ibict) began to create infrastructures, projects, and actions aimed at achieving the precepts defended by the aforementioned movements. The objective of this work is to indicate and describe the actions, projects, and infrastructures regarding scientific communication created and coordinated by Ibict in the context of open access and open science. This article presents a document research work with a qualitative approach, as analyses were performed on various types of sources. Since the beginning of the 2000s, Ibict has been working firmly to build the necessary infrastructures to promote open access and, more recently, open science. This effort is reflected on the 14 actions, projects, and infrastructures that were created and coordinated by or in partnership with the Institute. The infrastructures presented herein denote the effort undertaken by Ibict to promote scientific communication in an open and transparent manner. Complementary to each other, such infrastructures are capable of creating a national framework in favor of the pillars of open access and open science, highlighting Brazil on the international stage.